Pengaruh Model Project Based Learning Terhadap Keterampilan Berpikir Kreatif Peserta Didik Dalam Pembelajaran Fisika Materi Momentum Dan Impuls - Firda Maulida Firdaus; Endang Surahman; Yanti Sofi Makiyah (Jurnal Penelitian Pembelajaran Fisika, 2022)
models and the low creative thinking skills of students in momentum and impulse materials. In an effort to overcome these problems, the researchers applied one of the learning models, namely the project based learning model. This study aims to determine the effect of the project based learning model on students' creative thinking skills in learning physics on momentum and impulse materials. This research was conducted at MA-YIA Panembong located in Rajapolah, Tasikmalaya Regency from September to October 2021. The research method used was a quasi-experimental design with a posttest-only control group design. The sample in this study was taken by simple random sampling consisting of class X IPA 2 as the experimental class and X IPA 1 as the control class. The instrument used is a test instrument in the form of an essay question and a non-test instrument in the form of an observation sheet on the implementation of the project based learning model. Based on the results of hypothesis testing on posttest data using the t-test, it can be concluded that H0 is rejected and H1 is accepted. That is, the application of the project based learning model has been proven to have an effect on students' creative thinking skills in learning physics on momentum and impulse materials. The overall project-based learning model implementation sheet is in the very good category with an average percentage value of 95%. This shows that in the learning process the researcher consistently applies the project-based learning model syntax